La expresión oral y los libros de texto. Estudio de los manuales escolares de Ed. Primaria para conocer el número de actividades orales de las distintas editoriales - Suárez Ramírez, Miriam (Investigaciones Sobre Lectura, 2016)
We all know the importance of oral and communication skills and the difficulties presented by our children and youth to make use of them. On the other hand, we continue checking the importance of exercise textbooks or textbooks in schools. To this it is added that still too often teachers still considers these textbooks or textbooks as the main resource to organize their teaching-learning process. We believe the textbooks or textbooks remain a very important tool for students and teachers weight. So, what these books or manuals will propose what then put into practice in the school daily. So we’ve looked at the primary school textbooks that are present in various colleges Ed. To analyze the extent to propose activities that develop oral expression of students.